Hysteresis scaling relations in polycrystalline BaTiO3 bulk ceramics - N. Wongdamnern (2018)
The scaling behaviors of the dynamic ferroelectric hysteresis of polycrystalline BaTiO3bulk ceramics were investigated. To enhance the accuracy of prediction, not only sets of the scaling relation of hysteresis area 〈A〉 against frequency f and field amplitude E0were established, but also were sets of scaling relation of remnant polarization (Pr) and coercive field (EC) against frequency f and field amplitude E0. All scaling relations of hysteresis parameters, 〈A〉, Pr, and EC, displayed obviously the inter-correlation between f- and E0-exponents in both sub-coercive field and above coercive field conditions. By first approximation, the scaling relations took a form of Af-0.39E01.06, Prf-0.18E00.47, and ECf-0.33E00.46 above the coercive field condition; whereas the scaling relations in the form of Af-0.55E03.40, Prf-0.43E01.73, and ECf-0.27E01.35 were obtained under a sub-coercive field condition. The frequency observation range affected directly the scaling exponents. Over the same frequency range, the scaling relations obtained in this study are generally comparable to previously reported scaling behavior in BaTiO3single crystals, as well as in other polycrystalline bulk ceramics, suggesting that materials (both single and polycrystalline) with similar domain switching mechanisms should have comparable dynamic hysteresis and scaling behavior. © 2010 Elsevier B.V. All rights reserved.